2021
DOI: 10.7150/ijms.50967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Footwear and Foot Deformities in patients with Parkinson's disease: A Case-Series Study

Abstract: Background: Parkinson's disease (PD) is a common and complex neurological problem. Gait abnormalities are frequent in PD patients, and this increases the risk of falls. However, little is known about foot deformities and footwear in this vulnerable population. Here we investigate whether patients with PD use an appropriate shoe size and know if they have foot deformities or alterations. Methodology: A study of a series of observational descriptive cases in a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Postural and motor deficiencies are among the most incapacitating symptoms for patients with PD, disturbing their quality of life [19]. These conditions respond poorly to pharmacological treatment, so it is important to consider new actions and approaches [12]. The objective of this systematic review was to determine the effect of different types of insoles and footwear in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postural and motor deficiencies are among the most incapacitating symptoms for patients with PD, disturbing their quality of life [19]. These conditions respond poorly to pharmacological treatment, so it is important to consider new actions and approaches [12]. The objective of this systematic review was to determine the effect of different types of insoles and footwear in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The author hypothesized that this footwear modification could have a role in the treatment of gait dysfunction in PD. However, this type of intervention would not be recommended for most Parkinson's patients because of the high prevalence of equine foot in these patients-which is 71.7% according to an observational study conducted in 2021-which would hinder the efficacy and compliance with this treatment [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novo-Trillo et al analysed the feet of 53 patients with Parkinson's, resulting in 88.68% presenting some podiatric pathology, predominantly nail pathologies and presentation of the ankle joint in equine position. 8 Another study carried out in the United Kingdom with questionnaires in Parkinson's patients confirmed that 53% of the 218 patients interviewed presented problems in their feet, the most frequent being loss of sensitivity, weakness, limited movements in the feet/ankles and pain of feet. 9 In the study by Navarro-Flores et al, foot pain was the reason that most influenced the quality of life of patients with PD.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have analysed in Parkinson patients the quality of life in relation to the state of health of the foot, 5 the presence and levels of depression, 6 the fear of movement they experience, 7 all of these circumstances being affected by neurological disease with a negative impact. Novo‐Trillo et al analysed the feet of 53 patients with Parkinson's, resulting in 88.68% presenting some podiatric pathology, predominantly nail pathologies and presentation of the ankle joint in equine position 8 …”
Section: Introductionmentioning
confidence: 99%